Economics of Sustainable Development——Harmonisation of Resources and the Environment - Shi, Ge (Transactions on Economics, Business and Management Research, 2024)
This paper explores the economic theory of sustainable development and its application to the coordination of resources and the environment. It first describes the evolution of the concept of sustainable development and the main theoretical models, and analyses the relationship between resource scarcity and economic development, environmental issues and economic analysis. This is followed by a discussion of the implementation strategies of resource management policies and environmental protection policies, as well as the experiences and challenges of developed and developing countries in sustainable development. In particular, the current situation in China is analysed, and policy recommendations and future perspectives for promoting sustainable development in China are presented. Through comprehensive analyses, the paper aims to provide theoretical support and policy recommendations for promoting the coordinated development of economic growth and environmental protection.